QUALITATIVE STUDY: IMPLEMENTATION OF PROBLEM-BASED LEARNING MODEL TO IMPROVE STUDENTS' ACTIVE LEARNING IN LEARNING PHYSICS - Fadhila, Zakhia Jilan; Alé, Jhon Alfredo Silva (EduFisika: Jurnal Pendidikan Fisika, 2024)
This research was motivated by the results of students' low learning activity. The aim of this research is to determine the implementation of the problem based learning model in increasing students' active learning in physics learning. This research uses descriptive qualitative research methods. The research subjects were physics subject teachers at SMAN 15 Muaro Jambi with the subject selection technique used, namely purposive sampling. The data collection techniques used in this research were observation and interviews. Data analysis uses the Miles and Huberman data analysis technique which begins with data reduction, the data is then presented (data display), and finally verified (conclusion drawing) using survey and questionnaire techniques with a quantitative approach. The findings of this research show that implementing the problem-based learning model can enhance students' active learning. The conclusion is that this research aims to boost students' engagement in learning and can be regarded as an effective approach for increasing student participation and involvement in the physics learning process.